Endocrinopathies in celiac disease: When the endocrinologist sees what is invisible to the gastroenterologist - Khater, Dooa (Acta Biomedica Atenei Parmensis, 2018)
Celiac disease (CD) is a systemic, immune mediated and genetically determined small intestinal disorder characterized by intolerance to dietary gluten that generally presents with gastrointestinal symptoms in young children and extra-intestinal manifestations. Furthermore, there is close association between CD and endocrine diseases, including diabetes, autoimmune thyroid diseases, growth and pubertal disorders, etc. probably due to the presence of a common genetic predisposition. The present review aims to highlight and give more insight to the endocrine changes in CD, especially when there are few or no gastrointestinal symptoms and to emphasize on screening opportunities in some endocrine diseases.